Financial literacy and its consequences in the emerging middleclass - Antonia Grohmann; Roy Kouwenberg; Lukas Menkhoff (Kiel Institute for the World Economy (IfW), 2014)
This paper analyzes the state and impact of financial literacy in a so far largely neglected group: the middle class in emerging economies. This group is of increasing importance for implementing structural change, including the proper use of sophisticated financial products. We survey middle class people living in Bangkok and find that higher financial literacy leads to an increased probability of individuals demanding the sophisticated financial products that are available, and more informed use of credit cards. Overall, improving the financial literacy of the emerging middle class provides a double dividend: it increases the welfare of this group and also contributes to financial development, which is a driver of growth.
Keywords: D14; G11; G14; 330; Financial literacy; Saving; Borrowing; Development; Instruments